The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fenrg.2023.1194543
|View full text |Cite
|
Sign up to set email alerts
|

Can central and local forces promote green innovation of heavily polluting enterprises? evidence from China

Abstract: Adequate government environmental supervision is the key to promoting green innovation which is an essential driver of green development. In environmental decentralization, an analysis of the mechanism of the inherent influence of central and local supervision on green innovation may prove to be of practical importance. The paper selects data from heavily polluting enterprises in A-shares in China from 2013 to 2019 using fixed-effects models, moderating effect models, heterogeneity tests, and other research me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…In terms of the factors influencing green innovation, scholars focus on the effects of different factors such as regulation, economy, structure, and foreign openness on the efficiency of relevant green innovation. For example, the study conducted by Yang et al (2023) provides further evidence for the application of the "Porter hypothesis" in China. They found that both central and local environmental regulations significantly promote green innovation in heavily polluting enterprises, with central environmental regulation enhancing the effectiveness of local environmental regulation in driving green innovation.…”
Section: Literature Reviewmentioning
confidence: 94%
“…In terms of the factors influencing green innovation, scholars focus on the effects of different factors such as regulation, economy, structure, and foreign openness on the efficiency of relevant green innovation. For example, the study conducted by Yang et al (2023) provides further evidence for the application of the "Porter hypothesis" in China. They found that both central and local environmental regulations significantly promote green innovation in heavily polluting enterprises, with central environmental regulation enhancing the effectiveness of local environmental regulation in driving green innovation.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Certain scholars propose that design professionals, alongside engineering technical capabilities, should also possess skills in user analysis, market insights, and corporate innovation [22,23]. These studies emphasize that industrial design and new technologies are intertwined, necessitating knowledge and skills from psychology, sociology, economics, and other disciplines for effective integration with new technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers considered the ecological and environmental capacities for an interregional transfer of polluting industries [43]. Similarly, from an empirical data standpoint, one can establish that an environmental supervision path under collaboration by governments at different levels offers implications for achieving green innovation and optimizing pollution emission mechanisms [44]. Researchers adopted the MCDM approach in the decision making of a green and water-saving development in agriculture [45].…”
Section: Introductionmentioning
confidence: 99%